Reconstruction of the Values and Meanings of the “Jujur” Marriage Tradition among Millennials - Muna, Nailal; Fatmah; Wibowo, Bagus; Khowarizmi, Muhammad (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
This article aims to explore the phenomenology of the traditional jujur tradition that is still alive in the Musi River community amidst the dynamics of changing times. Jujur is a tradition in pre-wedding engagements when the groom's family gives a sum of money to the bride at the bride's request. This article aims to explore the social construction of jujur among the millennial generation born between 1980 and 2000. The research method uses empirical legal research methods with a structural approach. The research theory uses Peter. L. Berger's social construction. The research informants are community leaders and millennial generation husband and wife couples. The results of the article show the externalization of jujur in the form of giving money, noodles and gold and adapting to the economy and education of women, the objectification of jujur in the form of socialization that is so strong between generations that it creates an understanding that jujur is part of the marriage process and there are fines for violators of the engagement. The internalization of jujur is jujur as a symbol of male responsibility towards the family. The contribution of this research shows the existence of customary law as one of the sources of Indonesian national law, the treasure of interdisciplinary studies in the study of Islamic family law in Indonesia.